Microtus agrestis - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Microtus agrestis (Linnaeus, 1761). Fauna Suecica, 2nd ed., p. 11. TYPE LOCALITY: Sweden, Uppsala. DISTRIBUTION: Britain and nearby small islands, Scandinavia, and France east through Europe and Siberia to Lena River; south to Pyrennes of France and Spain, and to N Portugal; east to N Yugoslavia, S Urals, Altai Mtns, NW China (Xinjiang), and Lake Baikal region (Corbet, 1978c; Krapp and Niethammer, 1982). SYNONYMS: angustifrons, arcturus, argyropoli, argyropuli, argyropuloi, armoricanus, bailloni, campestris, britannicus, carinthiacus, enez-groezi, estiae, exsul, fiona, gregarius, hirta, insularis, intermedia, latifrons, levenedii, luch, macgillivrayi, miai, mongol, neglectus, nigra, nigricans, ognevi, orioecus, pannonicus, punctus, rozianus, rufa, scaloni, tridentinus, wettsteini. COMMENTS: Subgenus Agricola, agrestis species group sensu Zagorodnyuk (1990). Although regarded as conspecific with North American M. pennsylvanicus on morphological grounds (Klimkiewicz, 1970), chomosomal differences led Vorontsov and Lyapunova (1986) to conclude that their similarities represented convergence, not phylogenetic alliance; instead they remarked upon possible closer relationship of M. agrestis to North American M. chrotorrhinus. Zagorodnyuk (1990) emphasized this evolutionary distance by placing M. pennsylvanicus in the subgenus Mynomes. Chromosomal data summarized and reviewed by Zima and Krâl (1984a); European populations reviewed by Krapp and Niethammer (1982). Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 518, DOI: 10.5281/zenodo.7353098